Anonymous Bloggers and Defamation: Balancing Interests on the Internet - S. Elizabeth Malloy (Washington University Law Review, 2006)
As more and more people create personal websites and blogs, courts are more frequently asked to rule on questions related to the Internet boom. Specifically, an issue has arisen concerning what standard to apply in defamation suits brought against anonymous bloggers.9 Courts have wrestled with producing an appropriate standard for revealing the identity of an anonymous blogger who posts allegedly defamatory material on a message board or website. Recently, in Doe v. Cahill, the Delaware Supreme Court created a strict standard that makes it extremely difficult for defamation victims to bring suit against anonymous bloggers. The standard created is far too sympathetic to anonymous bloggers and fails to address important issues facing victims of defamation.
Keywords: Internet; Libel & amp; slander; Blogs; United States